The Effectiveness of the Environment Agency in Waste Management in the Province of the Special Capital Region of Jakarta - Nurul Aulia Pamungkas (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study discusses the Effectiveness of the Environmental Service in Waste Management in the Province of the Special Capital Region of Jakarta. The purpose of this research is to find out and examine how the waste management carried out by the Environmental Service of the Special Capital Region of Jakarta has been effective or not optimal. The theory used in this research is Hasibuan's Effectiveness (2003) with four dimensional variables which include performance quality, quantity of work results, time utilization and improvement of human resource outcomes. This study uses a qualitative descriptive method with data collection techniques carried out through interviews, observations and documentation studies. The results showed that the Environmental Service of the Special Capital Region of Jakarta in waste management has been effective in the dimensions of work quality by carrying out several innovative waste management efforts, utilizing time where the employees of the Environmental Service of the Special Capital Region of Jakarta empower the community to cooperate in waste management and discipline of employees regarding working time, as well as improving human resources through several mentoring programs and joint training. However, it is not effective in terms of the quantity dimension of performance results where the Bantargebang TPST is starting to experience excess capacity and the increasing pile of garbage in the province of Jakarta.